Managing Internationalization in a Complex Research Landscape - Shih , Tommy (International Higher Education, 2020)
Universities seeking to produce relevant research need to be involved internationally. This creates opportunities, but also causes clashes related to research norms and practices. A new tool set is needed in order to internationalize research responsibly.